Comparison of Stool Antigen Test with Histopathology of Endoscopic Gastric Biopsies for Detection for Helicobacter Pylori; A Hospital-Based Study - Zubair, Muhammad; Nawaid, Muhammad Amir; Afridi, Nabeel Khan; Baig, Bilal; Hanif, Muhammad; Mahmoud, Tamer Mohamed; Gabalunos, Helman Sansaet (Pakistan Armed Forces Medical Journal, 2022)
Objective: The objective of this study is to evaluate the diagnostic accuracy of H. pylori Stool Antigen (HpSA) test keeping histopathology as gold standard. Study Design: This is a cross sectional observational study. Place and Duration: This study was performed from Jan 2015 to Mar 2020 at Najran Armed Forces Hospital, kingdom of Saudi Arabia. Methodology: Total 151 patients in whom HpSA was done were included in the study. They were followed for their results of histopathology on gastric biopsies. Results: Among 151 patients 85(56.3%) were females and 66 (43.7%) were males. Mean age was 40 years. Forty three (28.5%) patients were positive for both HpSA and on histology, Fifteen (9.9%) patients were positive on HpSA test but negative on histology. Twenty two (14.6%) patients were negative on HpSA but they were positive on histology. Seventy one (47%) patients were negative both on HpSA and histology. The sensitivity and specificity were 66.1% and 82.5% respectively. Positive predictive value (PPV) was 74.1% and negative predictive value (NPV) was 76.3% for HpSA. Diagnostic accuracy for this test was 75.5%. Conclusion: Keeping in view the low sensitivity and diagnostic accuracy HpSA test cannot be used as screening tool in all patients, however it can be used for clinical correlation in setups where other diagnostic tests are not available due to the simplicity of its use, low cost and easy repeatability